Circadian Rhythms of Oxidant-Antioxidant Agents, HPA Axis and Protein Carbonyl Content in Serum, Brain and Adrenal Gland Tissues - Sabea Abed; Saad Alrawi; Tahani Al-Azawi (مجلة الانبار للعلوم البيطرية)
The aim of this experiment is to study the circadian rhythm of oxidant-antioxidant components in the body. A total of 20 adult male rabbits were divided into 2 groups (G1and G2)and kept in 2 different rooms. Serum was isolated after blood collection at 12 A.M or 12 P.M respectively from G1 and G2.The results reveal a significant elevation in serum GSH, MDA and SOD during night hours. The B-endorphin showed a value of 84.36±1.36 in rabbits serum during night compared with 53.23±1.12 during day hours. Serum ACTH and cortisone concentration during night hours expressed a value of 71.03±0.16 and 24.46±0.38 compared to 52.80±0.37 and 11.80±0.57 during day hours respectively. Protein carbonyl contents shows a regular variation between serum and tissues during day and night hours. It was concluded that the oxidant-antioxidant imbalance lead to such variation between day and night hours due to activities and metabolism. Extensive research is needed to minimize and overlap such stress.